Respuesta :

Answer:

x = 0

x = -4

x = -3

Step-by-step explanation:

Hello!

First, lets factor out 3x (GCF) from the whole expression:

  • [tex]f(x) = 3x^3 + 21x^2 + 36x[/tex]
  • [tex]f(x) = 3x(x^2 + 7x + 12)[/tex]

Factor the polynomial by grouping:

  • [tex]f(x) = 3x(x^2 + 7x + 12)[/tex]
  • [tex]f(x) = 3x(x^2 + 3x + 4x + 12)[/tex]
  • [tex]f(x) = 3x(x(x+3) + 4(x + 3))[/tex]
  • [tex]f(x) = 3x(x + 4)(x + 3)[/tex]

Set the expression and each factor to 0, and solve for x:

  • [tex]0 = 3x(x + 4)(x + 3)[/tex]

3x = 0

  • x = 0

x + 4 = 0

  • x = -4

x + 3 = 0

  • x = -3

There are 3 roots for this equation: 0, -4, and -3.

ACCESS MORE